Study on Improvement of Indonesia Shipbuilding Productivity with Theory of Constraints - Hirofumi Doi; Takeshi Shinoda (Institut Teknologi Sepuluh Nopember, 2018)
Indonesia is a big country having big population, huge area and huge Exclusive Economic Zone area. For world harmonized growth, it is quite important to realize steady economy growth on Indonesia. Growth of Indonesia’s shipbuilding industry specifically is an important part to achieve Indonesia’s maritime vision, but by far as for the shipbuilding market, 3 major countries, China, South Korea and Japan have obtained almost 100% share, which means it is quite difficult to increase the world share. In the volatile marine world, fluctuating oil price often affect production capacity, and investment decision is hard to get with TOP management. Indonesia shipbuilding industry has big mission under severe management and environmental condition. We clarify basic dilemma / conflict inhibiting the growth of Indonesia shipbuilding industry under assumption of severe management environmental condition, with Theory of Constraints (TOC). The basic dilemmas are solved by erasing the reason of existence of opposite activity and the Indonesia shipbuilding ever-lasting development logic is proposed with the solution of basic dilemma.